OPTIMAL MANAGEMENT OF JATIGEDE RESERVOIR FOR WATER SUPPLY SYSTEM DEVELOPMENT IN CIREBON RAYA METROPOLITAN - Medina, Rizka
Based on The Regional Regulation of West Java Province No. 12 of 2014, West Java Province developed a metropolitan area called the Metropolitan Cirebon Raya. Development of water supply system must be done, because drinking water demand will keep on increasing in line with the population growth. Jatigede Reservoir has potential as a source of raw water for SPAM Regional Metropolitan Cirebon Raya. The design criteria required for allocation of raw water (DMI) is 10-20 years on dry season i.e. at Jatigede Reservoir respectively 30.978 m3/s and 22.587 m3/s. This avaibility meets the planned of drinking water allocation for Water Supply System Development (3,5 m3/s). Then based on the quality, Jatigede Reservoir has fulfilled Government Regulation No. 82 of 2001 for the classification of first-class water quality. Jatigede Reservoir is a multipurpose reservoir. This is evidenced by the capacity of The Jatigede Reservoir design in the wet season and optimal in the Hurst Phenomenon method with a periode of one year. The optimal management of Jatigede Reservoir is expected to be carried out so reservoir’s constraints and objectiity can be met. Simulation of the optimal management pattern of Jatigede Reservoir using the Markov Discrete model of 5 (five) classes produces a graph with the value of correlation between the guidance trajectory and the actual trajectory of 0.941. This simulation with the Markov Discrete model is proven conceptual because it produces a correlation value between the guidance trajectory and the actual trajectory approaching the value of one, has fulfilled Government Regulation No. 37 of 2010, and fulfiled reservoir’s constraints and objectivity. Upstream Water Supply System configurations planned in the form of movable intake (pontoon), intake pipes, and transmission system.